Antarctica, human rights and international legal responsibility: Ukraine’s legal perspective from the Akademik Vernadsky Station - Ciornii, Inesa (Одеса : Фенікс, 2026)
The pressing need remains to improve the international legal regulation of researchers’ rights and safety. Mechanisms of states’ international legal framework governing researchers’ rights and safety, ensuring that mechanisms of state responsibility effectively protect both the natural environment and personnel. The operational experience of the Akademik Vernadsky Station underscores Ukraine’s contribution to global scientific cooperation and highlights the importance of codifying binding protection for Antarctic researchers. Adoption of a supplementary Antarctic Treaty protocol should be proposed by establishing standardized protections for scientific personnel, including enforceable safety standards, minimum due process guarantees, and real-time monitoring obligations for station-operating states.
Ciornii I. Antarctica, human rights and international legal responsibility: Ukraine’s legal perspective from the Akademik Vernadsky Station. Соціально-політична та правова система України в цифрову епоху: сучасні виклики : матеріали Міжнар. наук.-практ. конф. (м. Одеса, 22 квіт. 2026 р.) : у 2-х т. / заг. ред. С. Ківалова ; НУ «Одес. юрид. академія». Одеса : Фенікс, 2026. Т. 1. С. 274-278. URL: https://doi.org/10.32837/11300.33361
Keywords: Антарктида; міжнародне право; права людини; міжнародна правова відповідальність; станція «Академік Вернадський»; безпека науковців; Antarctica; international law; human rights; international legal responsibility; Akademik Vernadsky Station; researcher safety